“Can Nature Heal and be a Possible Remedy for the Management of Covid-19?” - Karthika, Chenmala; Sureshkumar, Raman (Infectious Disorders - Drug Targets, 2021)
The Covid-19 pandemic has become a major challenge for health care professionals and researchers all over the world. The discovery and development of new drugs require time for passing the quality, safety, and efficacy criteria. Hence the only available option is to rely on herbal or natural remedies as well as other existing ones. Nature has its healing power and has the remedy for all the ailments from which life on earth is struggling. For this pandemic situation also, nature should have created a remedy but finding a loophole is in the hands of our researchers. In this hypothesis, a novel combination strategy is introduced with the existing drugs such as hydroxychloroquine and flavonoid in a volatile liquid-based Nanoformulation incorporated into an inhaler as a possible remedy for the management of coronavirus infection. The synergistic activity of this combination shall pave the way for an effective therapeutic strategy for the treatment of COVID-19 symptoms.
Keywords: COVID-19